Kekatolikan Redup Karena Sekularisme? : Argumen Apologetik Jean-Luc Marion - Atawolo, Andreas B.; Borgias, Fransiskus (Parahyangan Catholic University, 2023)
This article presents Marion’s apologetic arguments about the maturity of Catholicity in facing secularism. He believes that secularism, which impacts moral decadence and the hegemony of secular political power, does not extinguish the spirit of Catholicity but becomes a Catholic moment—a chance for her to bear witness to the radicality of love. Authors use the qualitative research method, by making comparison between the theological results-study of Marion and some other theologians’ study and research (Balthasar, Kevin Hart, and Peter-Ben Smit), after having critically read their theological arguments. The results can be put forward in the following dialectical points of theological arguments. The Catholic Church has a matured experience in living a community of love based on the generous love of the Father. The Church demonstrates its responsibility in the world while contemplating the perfect City of God. The Church is not anti-political but simultaneously does not adhere to the hegemony of power. Throughout history, it has struggled to make a clear separation between religion and the state. The Church embraces the world with its two arms, namely, the Word and the Eucharist.